Effects of cow manure ratios on methane production and microbial community evolution in anaerobic co-digestion with different crop wastes - Hao, Jianjun; Jia, Shufei; Sun, Hao; Chen, Gaopan; Zhang, Jiaxing; Zhao, Yubin; Song, Yang; Zhao, Jianguo; Wang, Yaya; Liu, Shuang (International Journal of Agricultural and Biological Engineering, 2022)
The present study investigated the effects of cow manure ratios mixed with maize stover, rice straw, and wheat stalk at 3, 2, 1 (total solid based, TS-based), respectively, on methane production and microbial community structure during the anaerobic co-digestion process. Results showed cow manure co-digested with maize stover, wheat stalk, and rice straw at ratios of 2, 1, and 3 had the highest cumulative methane yields (272.99, 153.22 167.73 mL/g volatile solid (VS), respectively) and better stability (e.g. pH, volatile fatty acids (VFAs) and their component). The main microbe evolution had a similar trend which was Petrimonas and Methanosaeta in the early digestion process (Days 0-7) and then evolved into Longilinea, Ruminofilibacter, and Methanosarcina with the progress of digestion, but the relative abundance of these microbes in each reactor was different. It was worth noting that Caldicoprobacter in cow manure to maize stover ratio of 2, and to rice straw ratio of three reactors had a relatively higher proportion than reactor of cow manure to wheat stalk ratio of 1, and Hydrogenophaga was the specific bacterium in cow manure to wheat stalk ratio of 1 reactor. In addition, Petrimonas showed positive relationship with VFAs and Longilinea was the opposite. Methanosaeta and Methanobacterium contributed the most during the peak period of methane production in cow manure and maize stover co-digested reactor, and showed positive relationship with acetic acid. However, Methanosarcina and Methanospirillum made a great contribution during the peak period of methane production in cow manure co-digested with wheat stalk and rice straw reactors. These findings could provide further information on the application of cow manure co-digested with crop wastes. Keywords: cow manure ratio, methane production, microbial community evolution, crop wastes, anaerobic co-digestion DOI: 10.25165/j.ijabe.20221505.7148 Citation: Hao J J, Jia S F, Sun H, Chen G P, Zhang J X, Zhao Y B, et al. Effects of cow manure ratios on methane production and microbial community evolution in anaerobic co-digestion with different crop wastes. Int J Agric & Biol Eng, 2022; 15(5): 219–228.